Comparative Analysis of Metabolic Differences of Jersey Cattle in Different High-Altitude Areas - Kong, Zhiwei; Li, Bin; Zhou, Chuanshe; He, Qinghua; Zheng, Yuzhong; Tan, Zhiliang (Frontiers in Veterinary Science, 2021)
In high altitude area, hypoxia is a serious stress for humans and other animals, disrupting oxygen homeostasis and thus affecting tissue metabolism. Up to now, there are few reports on the metabolic changes of dairy cows at different altitudes. In this experiment, metabonomics technology and blood biochemical indexes were used to study the metabolic changes of dairy cows in different altitudes. The results showed that the different metabolites were mainly enriched in amino acid metabolism and sphingolipid metabolism, and sphingolipid metabolism showed negative correlation with increased altitude. The results of this study will enrich the hypoxia adaptive mechanism of dairy cows in high altitude areas, and provide a theoretical basis for the nutritional regulation of performance and disease treatment of dairy cows in high altitude areas.